Facile One-step Fabrication of Functional Cellulose Nanocrystals with High Efficiency under Microwave-ultrasound Synergy. (September 2020) - Lu, Qilin; Ran, Linlin; Chen, Shichao; Lu, Linna; Li, Lu; Li, Yonggui
Abstract: The use of cellulosic biomass for the manufacture of functional cellulose nanocrystals (FCNs) in a mild and green process is limited due to the multiple hydrogen bonds between cellulose. Based on the mechanochemical mechanism, an efficient and green approach to cleave hydrogen bonds and fabricate FCNs was realized via microwave-ultrasound synergy. In the one-step process, impact force, crash force, friction, chemical action, and thermodynamic interaction combined to create synergistic effects, accelerating the cleavage of hydrogen bonds and formation of FCNs synchronously. One-step purification of FCNs was implemented after reaction for the recovery of byproducts, which was critical to cost reduction and waste liquor treatment. FCNs with high crystallinity of 80%, high charge density, and good dispersion stability were obtained. Thus, a facile versatile green avenue for the large-scale production of FCNs was achieved in the study, and is expected to carry significant benefits in terms of economy and sustainability.